Common bean (Phaseolus Vulgaris L) micronutrient analysis - Mukankusi, Clare; Amongi, Winnyfred (2023)
The platform supports the common bean breeding programs within the Pan Africa Bean Research Alliance (PABRA) by phenotyping bean germplasm for seed iron and zinc content. Superior lines are promoted as high iron beans/ or utilized as parents for enhancing nutritional quality among popular bean market. The platform is also used to validate SeedFe and SeedFe levels in already released varieties in Africa to support programs that aim to promote biofortified bean. The platform is accessible to researchers working on beans in Africa that also includes Universities.